Soccer dog the movie - Marshall, James, 1967-; D'Abo, Olivia; Foley, Jeremy, 1983-; Giglio, Tony.; Forman, Daniel; Columbia TriStar Home Video (Firm) (Culver City, Calif. : Columbia TriStar, 2002)
It's only the second game of the season and the Stampede just lost a key player. Now only Lincoln's excellent forwarding skills can save the team from a forfeit and score a path to the championships. But will the PeeWee Soccer League let a dog play?
Title from disc surface.
Special features include: Digitally mastered audio & anamorphic video, theatrical trailers.
Directed by Tony Giglio; written by Daniel Forman; original music by Victoria Dolceamore.
James Marshall, Olivia d'Abo, Jeremy Foley.
Rated PG.
DVD, region 1, full screen presentation; Dolby Digital surround.
Keywords: Soccer for children -- Drama; Dogs -- Drama; Feature films; Comedy films; Children's films; Video recordings for the hearing impaired